Best Answer

I meant to ask Can you simplify 972=12^x (972 equals 12 to the x power)

Study guides

☆☆

Q: Can you simplify 972 equals 12x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

This will simplify to 27 - 12x, assuming the original equation was 7-34-2x-10x.* * * * *No, it will not! If the assumption is correct, it will simplify to -27-12x.

OK, SO 4x = 12x + 32.SO 4x -12x-12x-12x+32 (subtract 12x from each side to get x on one side)SO -8x = 32 (simplify)SO -1 (-8x) = 32 (-1) (multiply each side by -1)SO 8x -32 (simplify)SO 8x / 8 = -32/8 (divide each side by eight (8) to get ""X"" by itself)SO x= -4SO x = -4.Does that help?Hope that helps!

The answer to -12x minus 17 equals negative 89 is x equals 6.

108

12x = x + 3 11x = 3 x = 3/11

Related questions

It is: 12x

This will simplify to 27 - 12x, assuming the original equation was 7-34-2x-10x.* * * * *No, it will not! If the assumption is correct, it will simplify to -27-12x.

OK, SO 4x = 12x + 32.SO 4x -12x-12x-12x+32 (subtract 12x from each side to get x on one side)SO -8x = 32 (simplify)SO -1 (-8x) = 32 (-1) (multiply each side by -1)SO 8x -32 (simplify)SO 8x / 8 = -32/8 (divide each side by eight (8) to get ""X"" by itself)SO x= -4SO x = -4.Does that help?Hope that helps!

The answer to -12x minus 17 equals negative 89 is x equals 6.

108

12x = x + 3 11x = 3 x = 3/11

5x-3 = 11+12x 5x-12x = 11+3 -7x = 14 x = -2

12x - 8 = 10x + 42x = 12x = 6

12x + 6=9x + 27 12x-9x + 6=9x - 9x + 27 subtract 9x from both sides. 3x + 6 = 27 simplify 3x + 6 - 6=27 - 6 subtract 6 from both sides. 3x=21 simplify 3x/3=21/3 divide both sides by 3 x=7 simplify 12(7) + 6=>84+6=>90 9(7) + 27=>63+27=>90 It checks out!

divide numerator and denominator by 3x: 4/5

30+12x = 6(5+2x)

36 times 27 = 972 36 times 27 equals 972